A New Anti-acetylcholinesterase α-Pyrone Meroterpene, Arigsugacin I, from Mangrove Endophytic Fungus Penicillium sp. sk5GW1L of Kandelia candel - Huang, Xishan; Sun, Xuefeng; Ding, Bo; Lin, Ma; Liu, Lan; Huang, Huarong; She, Zhigang (Planta Medica, 2013)
Arigsugacin I (1), a new α-pyrone meroterpene, along with two known compounds, arigsugacins F (2) and territrem B (3), were isolated from the mangrove endophytic fungus Penicillium sp. sk5GW1L from Kandelia candel. Their structures were identified through mass spectrometry and NMR experiments, and the absolute configuration of compound 1 was further confirmed by low-temperature (100 K) single crystal X-ray diffraction with Cu Kα radiation. The absolute configuration of compound 2 was first reported by using X-ray copper radiation. Compounds 1–3 showed inhibitory activities against acetylcholinesterase with IC50 values of 0.64 ± 0.08 µM, 0.37 ± 0.11 µM, and 7.03 ± 0.20 nM, respectively.
Keywords: arigsugacin; territrem; Kandelia candel; Rhizophoraceae; Penicillium sp. fungus